2005
DOI: 10.1103/physrevd.72.114003
|View full text |Cite
|
Sign up to set email alerts
|

Color ferromagnetism of quark matter: A possible origin of a strong magnetic field in magnetars

Abstract: We show a possibility that strong "magnetic field" ∼ 10 15 G is produced by color ferromagnetic quark matter in neutron stars. In the quark matter a color magnetic field is generated spontaneously owing to Savvidy mechanism and a gluon condensate arises for the stabilization of the field. Since the quark matter is electrically charged in the neutron stars, the rotation of the quarks around the color magnetic field produces the strong "magnetic field".12.38. 12.38.Mh, 26.60.+c,97.60.Jd Quark Matter, Magnetar,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…Ifg > 1, the role of the external chromomagnetic field H is to enhance the effect of pion condensation that appeares in the model at µ ′ > 0 already at H = 0. For further investigations, it would be interesting to study the influence of an external chromomagnetic field (the gluon condensate) on the pion condensation phenomenon at nonzero current quark mass m as well as to consider the chromomagnetic catalysis effect with another combinations of a background field, different from (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ifg > 1, the role of the external chromomagnetic field H is to enhance the effect of pion condensation that appeares in the model at µ ′ > 0 already at H = 0. For further investigations, it would be interesting to study the influence of an external chromomagnetic field (the gluon condensate) on the pion condensation phenomenon at nonzero current quark mass m as well as to consider the chromomagnetic catalysis effect with another combinations of a background field, different from (20).…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently it was found that some combinations of external chromomagnetic and ordinary magnetic fields can penetrate into a bulk of the CSC medium and modify its ground state, producing a new type of color superconductivity [19]. Finally, note that in the dense quark matter, a superstrong magnetic field is originated due to the presence of the gluon condensate [20]. In conclusion, we see that there exist several new physical effects that are intrinsically connected with the gluon condensate (external chromomagnetic fields).…”
Section: Introductionmentioning
confidence: 99%
“…colour superconductivity with colour-flavor locking (Ouyed et al 2006), are not expected in solid quark stars as the quarks in such stars cannot be treated as free fermion gas any more. The magnetic field of a solid quark star will also be quite different (Xu 2005) from that of a traditional quark star (Iwazaki 2005) because of the different magnetic origins (Chen et al 2007;Xu 2005). The equation of state is very stiff in the solid quark star model, which is favored by the discovery of massive pulsars ( ally, the peculiar X-ray flare and the plateau of γ-ray burst could be relevant to a solid state of quark matter (Xu & Liang 2009;Dai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ferrario and Wickammasinghe [8] suggest that the extra strong magnetic field of the magnetars results from their stellar progenitor with a high magnetic field core. Iwazaki [9] proposed that the huge magnetic field of the magnetars is some color ferromagnetism of quark matter. Recently, Vink and Kuiper [10] have suggested that the magnetars orginate from rapid rotating protoneutron stars.…”
Section: Introductionmentioning
confidence: 99%